Enantiomers of flurbiprofen can distinguish key pathophysiological steps of NSAID enteropathy in the rat. Issue 6 (1st December 1998) - Mahmud, T; Somasundaram, S; Sigthorsson, G; Simpson, R J; Rafi, S; Foster, R; Tavares, I A; Roseth, A; Hutt, A J; Jacob, M; Pacy, J; Scott, D L; et al.
Abstract : Background —Non-steroidal anti-inflammatory drugs (NSAIDs) cause gastrointestinal damage by a non-prostaglandin (PG) dependent "topical" action and by inhibiting cyclooxygenase. Aims —To discriminate between these two effects by studying some key pathophysiological steps in NSAID enteropathy following administration of ( R )- and ( S )-flurbiprofen, the racemic mixture, and an uncoupler, dinitrophenol. Methods —The effects of dinitrophenol, racemic, ( R )-, and ( S )-flurbiprofen on mitochondria were assessed in vitro and on key pathophysiological features of small intestinal damage in vivo (ultrastructure by electron microscopy, mucosal prostanoid concentrations, intestinal permeability, inflammation, and ulcer count) in rats. Results —All the drugs uncoupled mitochondrial oxidative phosphorylation in vitro, caused mitochondrial damage in vivo, and increased intestinal permeability. Dinitrophenol and ( R )-flurbiprofen caused no significant decreases in mucosal prostanoid concentrations (apart from a decrease in thromboxane (TX) B2 concentrations following ( R )-flurbiprofen) while racemic and ( S )- flurbiprofen reduced mucosal prostanoids significantly (PGE, TXB2, and 6-keto-PGF1α concentrations by 73–95%). Intestinal inflammation was significantly greater following administration of ( S )-flurbiprofen and racemate than with dinitrophenol and ( R )-flurbiprofen. No small intestinal ulcers were found following dinitrophenol or ( R )-flurbiprofen while both racemic and ( S )-flurbiprofen caused numerous ulcers. Conclusions —Dinitrophenol and ( R )-flurbiprofen show similarities in their actions to uncouple mitochondrial oxidative phosphorylation in vitro, alter mitochondrial morphology in vivo, increase intestinal permeability, and cause mild inflammation without ulcers. Concurrent severe decreases in mucosal prostanoids seem to be the driving force for the development of severe inflammation and ulcers.